Identification and selection of immunodominant B and T cell epitopes for dengue multi-epitope-based vaccine - Lim, Hui Xuan *; Lim, Jian Hua *; Poh, Chit Laa * (Springer, 2021)
Dengue virus (DENV) comprises four serotypes (DENV1–4) which cause 390 million global infections with 500,000 hospitalizations and 25,000 fatalities annually. Currently, the only FDA approved DENV vaccine is the chimeric live-attenuated vaccine, Dengvaxia®, which is based on the yellow fever virus (YFV) genome that carries the prM and E genes of the respective DENV 1, 2, 3, and 4 serotypes. However, it has lower efficacies against serotypes DENV1 (51%) and DENV2 (34%) when compared with DENV3 (75%) and DENV4 (77%). The absence of T cell epitopes from non-structural (NS) and capsid (C) proteins of the yellow fever vaccine strain might have prevented Dengvaxia® to elicit robust cellular immune responses, as CD8+ T cell epitopes are mainly localized in the NS3 and NS5 regions. Multi-epitope-based peptide vaccines carrying CD4+, CD8+ T cell and B cell epitopes represent a novel approach to generate specific immune responses. Therefore, assessing and selecting epitopes that can induce robust B and T cell responses is a prerequisite for constructing an efficient multi-epitope peptide vaccine. Potent B and T cell epitopes can be identified by utilizing immunoinformatic analysis, but the immunogenicity of the epitopes have to be experimentally validated. In this review, we presented T cell epitopes that have been predicted by bioinformatic approaches as well as recent experimental validations of CD4+ and CD8+ T cell epitopes by ex-vivo stimulation of PBMCs with specific peptides. Immunoproteomic analysis could be utilized to uncover HLA-specific epitopes presented by DENV-infected cells. Based on various approaches, immunodominant epitopes capable of inducing strong immune responses could be selected and incorporated to form a universally applicable multi-epitope-based peptide dengue vaccine.